The Hedyotis diffusa chromosome-level genome and multi-omics analysis provide new insights into the iridoids biosynthetic pathway - Chen, Pengyu; Huang, Zhuang; Yin, Mingzhu; Wen, Yu-xin; Jiang, Qi; Huang, Ping; Qian, Rui; Hong, Xing; Zhu, Kaojiang; Xiao, Benjiang; Chen, Meng; Li, Shihao; et al. (Frontiers in Plant Science, 2025)
IntroductionHedyotis diffusa (Rubiaceae) is a medicinal herb with significant therapeutic potential, primarily attributed to its bioactive iridoid compounds. However, the molecular mechanisms governing iridoid biosynthesis in this species remain poorly characterized, limiting its biotechnological and pharmaceutical applications.MethodsWe generated a telomere-to-telomere (T2T) chromosomal-scale genome assembly of Hedyotis diffusa (∼482.30 Mb, anchored to 16 chromosomes) and performed phylogenetic and comparative genomic analyses to investigate its evolutionary history. Additionally, we analyzed the expression patterns of 30 methylerythritol 4-phosphate/mevalonate phosphate (MEP/MVA) pathway genes and 93 iridoid biosynthesis-related genes across different tissues. Gene tree clustering and gene expression analysis were employed to identify candidate genes involved in iridoid post-modification.ResultsThe genome assembly revealed a recent species-specific whole-genome duplication (WGD) event in Hedyotis diffusa. Expression profiling showed that MEP/MVA pathway genes were predominantly expressed in roots, while iridoid biosynthesis genes exhibited tissue-specific patterns. Three candidate genes—LAMT, OAT, and CYP71—were implicated in iridoid post-modification processes. Gene tree clustering further identified one LAMT gene (Hd_18862) and two CYP71D55 homologs (Hd_18118 and Hd_18119) as key contributors.DiscussionThis study provides the first T2T genome resource for Hedyotis diffusa, elucidating its unique WGD event and evolutionary trajectory. The tissue-specific expression patterns of MEP/MVA and iridoid biosynthesis genes suggest spatial regulation of metabolite production. The identification of LAMT and CYP71D55 homologs advances understanding of iridoid structural diversification. These findings establish a genomic foundation for further exploration of iridoid biosynthesis mechanisms and potential metabolic engineering applications.